Facade, Bharat Bhawan - Ghosh, Ayan (2023)
Bharat Bhavan on Currimbhoy Road is named after the Bharat Petroleum Corporation Limited, which has offices here and owns the building. The building was completed in the 1930s and is entered through a cantilevered porch which is typical of the period and features in many Art Deco buildings in Mumbai.